2021
DOI: 10.1002/smll.202104551
|View full text |Cite
|
Sign up to set email alerts
|

Bright Electroluminescent White‐Light‐Emitting Diodes Based on Carbon Dots with Tunable Correlated Color Temperature Enabled by Aggregation

Abstract: Carbon dots (CDs) as one of the most promising carbon‐based nanomaterials are inspiring extensive research in optoelectronic applications. White‐light‐emitting diodes (WLEDs) with tunable correlated color temperatures (CCTs) are crucial for applications in white lighting. However, the development of high‐performance CDs‐based electroluminescent WLEDs, especially those with adjustable CCTs, remains a challenge. Herein, white CDs‐LEDs with CCTs from 2863 to 11 240 K are successfully demonstrated by utilizing agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…It was also observed that V on (defined as the voltage at 1 cd m −2 ) of both the pure poly-TPD and poly-TPD:TFB single-component ZnO-WLEDs is around 2 V, which is much smaller than those of other types of WLEDs. 16,17,19,35–37 Thus, the EL performance of the present devices is best among that of the single-component ZnO-WLEDs reported so far. Moreover, the optimized L max in the single-component ZnO-WLEDs based on poly-TPD:TFB is nearly twice that in the neat poly-TPD-based devices.…”
Section: Resultsmentioning
confidence: 69%
“…It was also observed that V on (defined as the voltage at 1 cd m −2 ) of both the pure poly-TPD and poly-TPD:TFB single-component ZnO-WLEDs is around 2 V, which is much smaller than those of other types of WLEDs. 16,17,19,35–37 Thus, the EL performance of the present devices is best among that of the single-component ZnO-WLEDs reported so far. Moreover, the optimized L max in the single-component ZnO-WLEDs based on poly-TPD:TFB is nearly twice that in the neat poly-TPD-based devices.…”
Section: Resultsmentioning
confidence: 69%
“…The optimal CIE coordinates (0.333, 0.397) were obtained by developing the WLED guided by XGB of the ML model. CIE coordinates (0.333, 0.397) are located in the center of the nearby, showing an excellent white light, which corresponds to a good color temperature (CCT) of 5478.32 K. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…Unlike conventional quantum dots, such as CdTe, CdSe, PbSe, and GaAs, CDs do not contain environmentally harmful heavy metal ions, e.g., Cd, Pb, and As. [34][35][36][37][38] In our previous work, we demonstrated that combining blue-emitting carbon dots (BCDs) with Dy 3+ doped glasses could be an efficient way to generate white light emission and compensate for the low blue light emission of Dy 3+ ions. However, the PLQY values and colorimetric properties, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…, Cd, Pb, and As. 34–38 In our previous work, we demonstrated that combining blue-emitting carbon dots (BCDs) with Dy 3+ doped glasses could be an efficient way to generate white light emission and compensate for the low blue light emission of Dy 3+ ions. However, the PLQY values and colorimetric properties, e.g.…”
Section: Introductionmentioning
confidence: 99%